EFEKTIVITAS PENGELUARAN KESEHATAN DAN PENDIDIKAN PEMERINTAH UNTUK MENINGKATKAN INDEKS PEMBANGUNAN MANUSIA - Okta Rabiana Risma; Affandi Affandi; Rollis Juliansyah (JURNAL EKOMBIS, 2019)
This research aims to analyse how much influence the proportion of government expenditure on health and education as a supporting improvement of human development index in Aceh Province. The model used in the study was the panel data model i.e. from 2012 to 2013. As for in this research the variables are tested i.e. Government expenditure on health (KS) and government expenditure in education (PDK) as independent variables. Meanwhile, Human Development Index (HDI) as its dependencies variable. Based on regression gained that the best approach to the outcome of this study is fixed effect model. Health variables have a negative and insignificant influence on human development indices. While the educational variables are significant and positive to the HDI  in Aceh.Keywords: Panel model, Government expenditure, human development index.